2019
DOI: 10.1590/1982-0216/20192158519
|View full text |Cite
|
Sign up to set email alerts
|

Chewing and swallowing in obese individuals referred to bariatric surgery/gastroplasty - a pilot study

Abstract: Objective: to describe the chewing and swallowing pattern of obese individuals indicated for bariatric surgery/gastroplasty before the procedure, using standardized clinical protocols. Methods: a cross-sectional descriptive case-control study that presents preliminary data for a larger investigation. Eight participants matched for age and sex were divided into two groups (four in the research group and four as controls) and submitted to clinical speech therapy assessment using the “Questionnaire on eating beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…We found that patients with clinically severe obesity exhibited abnormalities in the functioning of the stomatognathic system, with less muscle activity of the masseter and temporal muscles than women without obesity. These results corroborate with Rocha et al in which orofacial myofunctional dysfunctions were more frequent in patients with obesity [7]. In a similar study, Veyrune et al compared the chewing parameters and found a lower masticatory performance in patients without and with obesity [3].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We found that patients with clinically severe obesity exhibited abnormalities in the functioning of the stomatognathic system, with less muscle activity of the masseter and temporal muscles than women without obesity. These results corroborate with Rocha et al in which orofacial myofunctional dysfunctions were more frequent in patients with obesity [7]. In a similar study, Veyrune et al compared the chewing parameters and found a lower masticatory performance in patients without and with obesity [3].…”
Section: Discussionsupporting
confidence: 84%
“…Some reports pointed to the impact of obesity, particularly clinically severe obesity, in the stomatognathic system, which seems less efficient than individuals with a normal weight [3][4][5][6]. Consequently, chewing efficacy in people with obesity can affect not only the mechanical process of nourishment but also the relationship between nutrition and eating behavior [7], since this condition contributes to the consumption of ultra-processed food with higher energy density and pastier and easier to be consumed [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested a relationship between chewing and weight gain [ 25 , 26 ], characterized by rapid chewing in individuals with severe obesity and/or those who have undergone bariatric surgery [ 27 , 28 , 29 ]. Some studies have shown that chewing quickly and less frequently is associated with obesity [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%